Prediksi pergerakan harga saham menggunakan analisis profitabilitas - Puspitaningtyas, Zarah (Faculty of Economics and Business Universitas Jenderal Soedirman, 2017)
Background: Stock price movements can be predicted using fundamental analysis based on the information presented in the company's financial statements. Based on the analysis, investors can measure the company's performance and predict the direction of stock price movements. Methodology: Prediction of stock price movement using profitability analysis was done by testing the effect of profitability to stock price. The intended stock price is the market price that occurs on the exchange at a certain moment determined by the market participants. Profitability in this study was measured by using indicator of return on asset, return on equity, net profit margin, and earnings per share. The study object is non-banking companies listed on the Indonesia Stock Exchange and listed in the LQ45 Index in the period of 2011-2016. The data were collected using purposive sampling technique. Furthermore, the data were analyzed using multiple linear regression method. Findings: At a significance level of 5%, the results of the analysis concluded that only earnings per share that has a significant effect on stock price. Meanwhile, the other three profitability indicators i.e. return on asset, return on equity, and net profit margin have no effect on stock price. Thus, the results of this study indicate that profitability measured using indicator of return on asset, return on equity, and net profit margin does not reflect stock price movements. In other words, stock price movements can only be predicted using earning per share indicator. Keywords: fundamental analysis, profitability, stock price.